2010
DOI: 10.2528/pierb10062407
|View full text |Cite
|
Sign up to set email alerts
|

Support Vector Machines for the Classification of Early-Stage Breast Cancer Based on Radar Target Signatures

Abstract: Abstract-Microwave Imaging (MI) has been widely investigated as a method to detect early stage breast cancer based on the dielectric contrast between normal and cancerous breast tissue at microwave frequencies. Furthermore, classification methods have been developed to differentiate between malignant and benign tumours. To successfully classify tumours using Ultra Wideband (UWB) radar, other features have to be examined other than simply the dielectric contrast between benign and malignant tumours, as contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 31 publications
2
74
0
Order By: Relevance
“…UWB tumour classification was examined by Chen et al [44][45][46][47][48] and Teo et al [49] using tumours located in 2D breast models, while studies by Davis et al [30] and Conceição [51][52][53][54][55], McGinley et al [56], O'Halloran et al [57] and Alshehri et al [64] considered tumours in 3D breast models. The latter will not be further discussed in this study since discrimination between benign and malignant tumours is only assessed in terms of dielectric differences between the two types of tumours and does not address resulting tumour signatures due to different shapes, which is the scope of this paper.…”
Section: Combining Breast and Tumour Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…UWB tumour classification was examined by Chen et al [44][45][46][47][48] and Teo et al [49] using tumours located in 2D breast models, while studies by Davis et al [30] and Conceição [51][52][53][54][55], McGinley et al [56], O'Halloran et al [57] and Alshehri et al [64] considered tumours in 3D breast models. The latter will not be further discussed in this study since discrimination between benign and malignant tumours is only assessed in terms of dielectric differences between the two types of tumours and does not address resulting tumour signatures due to different shapes, which is the scope of this paper.…”
Section: Combining Breast and Tumour Modelsmentioning
confidence: 99%
“…In studies by Conceição et al [51][52][53]55] and McGinley et al [56] a similar approach to that of Davis et al [30] is used. The main differences are the dimensions of the TF and SF regions, as illustrated in Figure 13.…”
Section: Combining Breast and Tumour Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature has shown that these and other similar classification techniques can be extended to microwave systems for breast cancer detection [6,[15][16][17][18], stroke detection [19], and bladder monitoring [20]. To date, the use of classifiers for breast cancer detection has focused on microwave systems using a numerical analysis; most recently the first experimental study, using frequency-domain measurements, was reported in [21].…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary classification methods investigated for breast cancer detection has been Support Vector Machines (SVM) [6,[16][17][18]. The analysis in [21] was concerned with classifying tumors by shape and size, and demonstrated that the size and shape category of a tumor can be determined correctly in more than 86% of cases.…”
Section: Introductionmentioning
confidence: 99%